Validation of the employability of entry-level HR graduates in the South African Labour context - Zeni, Marchelle Marelize (Vaal University of Technology, 2023)
Background Role players navigating the world of work must make timely paradigm shifts as work realities constantly change nationally and worldwide. After graduation, the conventional idea of being competent for entry-level positions has given way to the notion of employability, which is now crucial in the evolving workplace and implies the necessity for obtaining new skills and traits. Students no longer attend higher education institutions solely for the goal of academic advancement. It must be said that employability is a competitive edge in the South African labour market, which has a relatively low demand for new entrants. Today, automation and technology advancements have altered the nature of the labour market, where mismatches and skill shortages are being experienced as opposed to academic qualifications. In addition, the industry expressed concern over the fact that graduates do not always meet their demands and expectations and expect HEIs to align their curricula to promote employability. Universities also have difficulty producing skilled graduates since they place an undue emphasis on topic knowledge, which employers view as inadequate given the status of the economy today. Furthermore, HEIs find it challenging to stay abreast with the macro-environment changes and the continuously changing skills expectations of the industry. Some of the skill changes significantly impact workers and the companies they work for, with entry-level job seekers particularly affected. The employer’s expectations of entry-level graduates are high and are growing as they expect more and more from the new graduates. Aims This study investigates the validation of the employability of entry-level HR graduates in the South African labour context. The focus was centred around employers’ expectations and experiences. Relevant theoretical and empirical objectives supported the study’s primary objective. Methodology The study’s epistemological stance culminated in a positivist research approach. The invitation to participate in the study was distributed via the SABPPs monthly newsletter and social media platforms. Due to the implications of protecting private information (POPI Act) and the challenges of data collection during the COVID-19 pandemic, a non-probability (small-scale) self-selection sampling method resulted in a sample size of n=161 respondents. The configuration of Hinchliffe and Jollie’s (2011) “Graduate identity and employability” was adapted with their permission for this study. Consequently, a structured questionnaire, guided by the study’s empirical objectives, consisted of nine sections. Section A sought informed consent and Section B elicited the respondent’s demographic data. In sections C through H, questions about the experiences and expectations of the entry-level HR graduate were posed. Lastly, Section I explored how the COVID-19 pandemic affected respondents' expectations and experiences of entry-level HR graduates. Respondents indicated their answers using Google forms. In the initial pilot study (n=31 respondents), feedback received culminated in a refined and effective measuring instrument. The pilot studies’ reliability coefficients ranged from 0.757 to 0.976, which exhibited satisfactory reliability. In addition, these results indicate that the questionnaire was suitable for collecting information for the main inquiry. Aspects related to the statistical processes used and ethical considerations guiding the study were highlighted. Results and discussion Empirical conclusions reached were supported by the statistical analysis of the data and the discussion thereof. Descriptive statistics facilitated the determination of the employer’s (respondents) expectations (A) and their experiences (B) of the entry-level HR graduate. Frequencies and percentages emanating from sections C to H were presented in tables, charts, or figures. Each section consisted of A expectations and B experiences. Additionally, the mean, SD, minimum, maximum, skewness and kurtosis were used to explain the distribution of the results. The data as frequencies and percentages could be compared for the expectations and experiences of the various sections (sections C to H). This studys reliability coefficients presented alpha values ranging from 0.839 to 0.959, which shows satisfactory reliability. Thereafter, a t-test was conducted to determine the Cohen’s-d value. The results revealed a large effect across sections C to H. Finally, a t-test with a one-way ANOVA test was done. The detailed discussion of the findings discerned that respondents’ expectations (A) were higher throughout the study than their actual experiences (B). General Despite a plethora of lists that supposedly indicate skills needed by graduates to secure employment, there is little consensus amongst existing scholarship while defining skills and the concept of employability. The skills approach was identified as ‘old-fashioned’ and made way for the graduate identity approach to give a clear understanding of graduate employability. Through experiences, interactions and self-discovery during their time at HEIs, the graduates can build their graduate identity and with this identity they can present themselves to potential employers. Therefore, the graduate identity profile consists of more than just skills and attributes. Conclusions The findings highlight significant insight into employers’ expectations of entry-level HR graduates. The results show that employers place high expectations on HR graduates. Technological advancements and HR trends contribute to employers’ high expectations, which makes it difficult for an entry-level graduate to secure employment. The graduate’s transition from university to the labour market is influenced by these high expectations and the high unemployment rate that makes securing a job even harder. Obtaining a degree is no longer the main requirement of employers. Graduates are expected to develop outside-the-classroom competencies and more. The graduate is exposed to new knowledge through self-discovery and personal interactions with others. These interactions will grant the graduate an opportunity to build their graduate profile. Employers want young graduates to participate in mentoring programs, join a committee and do community service. In addition, the competencies acquired during their study at university must be demonstrated to have significant value for potential employers. Employers, therefore, have higher expectations of entry-level HR graduates than they did in the past. The study found that enhancing graduates' employability prospects requires more than merely preparing them for the workforce by giving them the required skills, attributes and subject knowledge. Graduates must also gain job experience at university and learn about the industry they want to work in. The graduate should be flexible, work remotely and be eager to learn as their circumstances change. According to the study's findings, employers demand a graduate identity that will suit their culture from day one and this identity is vulnerable to challenges and change. Recommendations The study’s findings and recommendations are significant for HEIs, the HR industry and HR graduates. Rather than concentrating solely on theoretical subject knowledge, it is recommended that the HR curricula include methodologies for skill development. The quality of the workforce's skills impacts the economy of SA. Therefore, it is recommended that HEIs consider the demands of a more comprehensive labour market, influenced by technological advancements, AI innovations and HR trends. These changes will require a workforce with higher skill levels. Further, it is recommended that HEIs and the industry collaborate to improve existing Work integrated learning (WIL) programmes to enhance graduate employability. This partnership can also build relevant and required competencies into the curriculum to benefit all role players. Graduates are encouraged to acknowledge that obtaining a degree is but one aspect of securing future employment. A proactive approach to learning and development could enhance their employability prospects as they advance. Taking ownership of their graduate identity profile could expand the graduates’ efforts, interactions and the process of self-discovery. Graduates should continuously learn new skills and obtain knowledge outside the classroom through part-time work and networking.
MM (HRM) (Department of Human Resource Management, faculty of Management Sciences), Vaal University of Technology.
Keywords: Employability; Graduate employability; Skills; Attributes; Broader attributes; Entry-level; Graduate identity; Dissertations, Academic -- South Africa.; Employability -- South Africa.; College graduates -- Employment.